First Report of Microalgae Associated with Velamen Aerial Roots of Epiphytic Orchids in the Philippines: Microalgae in Velamen Roots of Orchids in the Philippines - Arguelles, Eldrin (Journal of Tropical Life Science, 2025)
Velamen roots of epiphytic orchids are unique environment for growth and proliferation of rare and novel microalgal species. This taxonomic study presents the first floristic survey of microalgal communities inhabiting the velamen roots of epiphytic orchids (Vanda ampullacea, Vanda denisoniana, Vanda bensonii) in the Philippines, documenting these taxa for the first time in this unique aerial habitat as new distributional records for the country. Overall, 16 species of microalgae were described taxonomically, of which four species each were identified belonging to Cyanophyceae, Bacillariophyceae, and Chlorophyceae, while two species each for Trebouxiophyceae and Zygnematophyceae. The survey reports an additional of fifteen species (Chlorella vulgaris, Mucidosphaerium pulchellum, Chlorococcum infusionum, Desmodesmus abundans, Ankistrodesmus falcatus, Pediastrum angulosum, Cosmarium formosulum, Closterium moniliferum, Cocconeis euglypta, Diatoma vulgaris, Nitzschia palea, Fragilaria vaucheriae, Chroococcus minutus, Pseudanabaena minima, and Nostoc verrucosum) as new records of microalgae associated with velamen roots of orchids found in Asia. In addition, the study documented the existence of three rare microalgae, Mucidosphaerium pulchellum (H.C. Wood) C.Bock, Proschold & Krienitz, Pediastrum angulosum Ehrenberg ex Meneghini, and Cosmarium formosulum Hoff which are taxonomically described as new records in the Philippines. The floristic survey enriches the diversity of algae from velamen roots of epiphytic orchids and provides important taxonomic and distributional records of microalgae found in terrestrial plants in the Philippines.